CCD2: design constructs for protein expression, the easy way. Issue 8 (4th August 2021) - Murachelli, Andrea Giovanni; Damaskos, George; Perrakis, Anastassis
Abstract : CCD 2 is a software tool that aggregates sequence information for protein sequences (conservation, structure prediction, domain and disorder detection), enabling informed choices for expression‐construct design, the single‐click generation of PCR primers for cloning and easy data tracking. Abstract : Studying the function or structure of proteins usually requires the generation of many protein‐truncation constructs for recombinant expression, which is a tedious and error‐prone job. CCD 2 is a software tool designed to facilitate and automate this task. CCD 2 helps scientists by aggregating the information necessary to design protein‐expression constructs. This information includes sequence conservation, secondary structure prediction, domain(s) and disorder detection, post‐translational modifications and information on similar (domain) structures that are available in the Protein Data Bank. CCD 2 then allows users to easily choose the boundaries for protein constructs and automatically generates the primers necessary for construct amplification by polymerase chain reaction. Finally, CCD 2 provides a quick analysis of the properties of the chosen constructs, together with their DNA vector maps for bookkeeping. The features of CCD 2 are discussed step by step, showing that it can be a useful tool for laboratories that engage in recombinant protein production for any type of experiment, and in particular for structural biology studies.